DIFFERENTIAL ENTROPY OF ADSORPTION In Ca5Na3 SEOLITE - Juraeva Z.; Bazarbayev M.; Mamadaliev U. (Innovate Conferences, 2025)
For the first time the main energy characteristics of ammonia adsorption in zeolite Ca5Na3A (MSS-624) were determined by adsorption-microcalorimetric method, differential values of free energy and entropy of adsorption were calculated, as well as the correlation between adsorption-energy characteristics and crystallochemical structure of adsorbent was found and the detailed molecular mechanism of formation of ion-molecular clusters of ammonia with cations in zeolite in the whole region of filling of nano-structured pore space of adsorbent was revealed. The stepwise character of the entropy of ammonia adsorption is revealed. The extended low entropy region correlates with the number of sodium and calcium cations in the zeolite structure. The average molar integral entropy of ammonia adsorption on zeolite Ca5Na3A (MSS-624) was found to be -61 J/mol K and indicates that in the zeolite the mobility of ammonia molecules is lower than the liquid phase and close to the mobility of the solid phase, leading to a strong inhibition of the mobility of adsorption on ammonia cations.
Keywords: zeolite, adsorption, entropy, isotherm, temperature, microcalorimeter, ammonia.